Implicatures in Political Discourse on Indonesia Lawyers Club Show - Mutia El Khairat (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
Implicature in political discourse is one of interesting problem to be studied in linguistics. Sometimes, many politicians usesentences which imply something different than the literal meaning for certain political purposes. Mass media is one of intercessionbetween political doer and people, such as a talk show or dialogue of politics on television. Indonesia Lawyers Club is one of dialoguein television, which discuss about political issues in Indonesia. This article aimed at describing and explaining forms and kinds ofimplicature used in political discourse by using implicature theory from Grice (1975) and Gazdar (1979). The method use in collectingthe data is observational method and technique of Non Participant Observation (NPO) followed by recording and note takingtechnique. Furthermore, this study uses referential and pragmatic identity method in analyzing data. It is a descriptive research inwhich using a qualitative approach. The data of the research are taken from utterances as found in the political dialogue entitledIndonesia Lawyers Club, as TV programs. The result of research shows that implicature has found and used in political discourse inIndonesia Lawyers Club by breaking the cooperation principle in declarative and negative form, while interogative is not found inthis show. Besides, the use of implicature also found in the kinds of conventional implicature, generalized conversational andparticularized conventional implicature, and scalar implicature. Furthermore, the meaning of implicature consists of criticism,teasing, obscurity of meaning, image projection, agree, disagree, and euphemism. Pragmatics functions in implicature consist ofassertive, directive, expressive and commisive. Finally, the value in implicature consists of political value, those are self-image ofideology, power, aversion, democracy, and protection, and morality value.